Alcohol-induced Cushing syndrome: report of eight cases and review of the literature - Surani, Asif; Carroll, Ty B.; Javorsky, Bradley R.; Raff, Hershel; Findling, James W. (Frontiers in Endocrinology, 2023)
Introduction Alcohol-induced hypercortisolism (AIH) is underrecognized and may masquerade as neoplastic hypercortisolism [Cushing syndrome (CS)] obscuring its diagnosis. Objective and methods In order to characterize AIH, we performed a chart review of eight patients (4 males and 4 females; 2014-2022) referred for evaluation and treatment of neoplastic hypercortisolism — six for inferior petrosal sinus sampling, one due to persistent CS after unilateral adrenalectomy, and one for pituitary surgery for Cushing disease (CD). Five underwent dDAVP stimulation testing. Results All eight patients had clinical features of hypercortisolism and plasma ACTH levels within or above the reference interval confirming hypothalamic-pituitary mediation. All had abnormal low-dose dexamethasone suppression test and increased late-night salivary cortisol. Only one had increased urine cortisol excretion. In contrast to CD, the 5 patients tested had blunted or absent ACTH and cortisol responses to desmopressin. Two had adrenal nodules and one had abnormal pituitary imaging. Most patients underreported their alcohol consumption and one denied alcohol use. Elevated blood phosphatidyl ethanol (PEth) was required in one patient to confirm excessive alcohol use. All patients had elevations of liver function tests (LFTs) with AST>ALT. Conclusion AIH is an under-appreciated, reversible cause of non-neoplastic hypercortisolism that is indistinguishable from neoplastic CS. Incidental pituitary and adrenal imaging abnormalities as well as under-reporting of alcohol consumption further confound the diagnosis. Measurement of PEth helps to confirm an alcohol use disorder. Elevations of LFTs (AST>ALT) and subnormal ACTH and cortisol responses to dDAVP help to distinguish AIH from neoplastic hypercortisolism.